The influence of music tempo on changes in electrolytes by exercise intensity - Won, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Changes in musical factors such as rhythm, tempo, tone, harmony and dynamics cause direct bodily responses such as pulse, blood pressure, heart rate, brain wave and hormone secretion. As such it is proposed that music may be used therapeutically to effect positive changes in these functions. However there is relatively limited knowledge concerning the relationship between music tempo and exercise and physical and mental health. Therefore this research aimed to elucidate how electrolytes are changed when the music tempos of allegro M.M=132 and andante M.M=66 are heard during exercises when measured at exercise intensities. An additional aim was to determine the musical tempos suitable at each exercise intensity. Methods For this research, 10 male university students at the University in Incheon were selected as subjects. Two tempos, allegro and andante were each applied during an exercise program in which subjects participated for 30 minutes. Exercise intensities of VO2max 35% and VO2max 65% were evaluated using a gas analyser while running on a treadmill with gradually increasing exercise intensities. Blood was collected for analysis at rest, immediately following the exercise and 30 minutes after their recovery periods. The data were processed used using a paired- samples t-test for each group. Results / Discussion The results indicated that: 1.The use of music tempos produced a significant difference in the concentration of blood aldosterone for each of the exercise intensities.(p<.05) and 2. The use of music tempos produced a significant difference in the concentration of blood aldosterone between the exercise intensities.(p<.05). In conclusion, when exercising with the exercise intensity of VO2max 65%, the hearing of music tempos produced significant differences between groups in aldosterone concentration. When music tempos were heard, aldosterone showed significant differences for the music tempo of M.M=66 between the exercise intensities. It is judged that music with a fast tempos should be effective regardless of the exercise intensity. Also, this research suggested that both positive and negative outcomes occur when applying music of varying tempo during exercises. In conclusion when listening to two types of music tempo at exercise intensity VO2max 35% and 65%, there was a significant difference in aldosterone immediately after exercise and 30 minutes after rest during moderate exercise. During low to moderate exercise, music tempo may affect electrolytes and using music tempo is more efficient in moderate exercise than low. When listening to exercise intensity M.M=132 and M.M=66, aldosterone showed significant change immediately after exercise and 30 minutes after rest for M.M=66. The use of music tempo is not effective for slow tempo, and for exercise intensity VO2max 35% and 65%, while listening to music tempo during exercise only, music tempo of M.M=66 influences serum hormone level more effectively than music tempo of M.M=132 regardless of the exercise being of low or moderate intensity.